2017
DOI: 10.1021/jacs.7b06785
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II)-Catalyzed ortho-Selective Aminomethylation of Phenols

Abstract: A Cu(II)-catalyzed ortho-selective functionalization of free phenols with trifluoroborates to afford C-C coupling products under mild conditions has been developed. A variety of functional groups on the phenol and the potassium aminomethyltrifluoroborate substrates were found compatible, furnishing the corresponding products in moderate to excellent yields. A single-electron transfer radical coupling mechanism involving a six-membered transition state is proposed to rationalize the high levels of ortho-selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 71 publications
1
29
0
2
Order By: Relevance
“…Only nonbasic alkylmetal reagents can be used for the alkylation of free phenols because of their acidity.P otassium aminomethyltrifluoroborates meet this requirement, and the Wang group showed that they were efficient reagents for the copper-catalyzed ortho-aminomethylation of phenols (Scheme 34). [154] Upon reaction with catalytic amounts of copper(II) acetate and sodium acetate,arange of phenols could be readily aminoalkylated in an open flask regardless of the electronic and steric properties of the starting phenols; however, meta-substituted ones gave mixtures of regioisomers.T he mechanism proposed involves the formation of acopper(II) phenoxide that coordinates to the nitrogen atom of the aminomethyltrifluoroborates.F urther oxidation by copper(II) species generates aboron radical whose homolytic cleavage yields ac arbon-centered radical that then adds to the phenol with concomitant reduction of copper(II). Rearomatization and decoordination of the alkylated phenol followed by oxidation of copper(I) to copper(II) finally close the cycle.…”
Section: Alkylation With Alkylmetal Reagentsmentioning
confidence: 99%
“…Only nonbasic alkylmetal reagents can be used for the alkylation of free phenols because of their acidity.P otassium aminomethyltrifluoroborates meet this requirement, and the Wang group showed that they were efficient reagents for the copper-catalyzed ortho-aminomethylation of phenols (Scheme 34). [154] Upon reaction with catalytic amounts of copper(II) acetate and sodium acetate,arange of phenols could be readily aminoalkylated in an open flask regardless of the electronic and steric properties of the starting phenols; however, meta-substituted ones gave mixtures of regioisomers.T he mechanism proposed involves the formation of acopper(II) phenoxide that coordinates to the nitrogen atom of the aminomethyltrifluoroborates.F urther oxidation by copper(II) species generates aboron radical whose homolytic cleavage yields ac arbon-centered radical that then adds to the phenol with concomitant reduction of copper(II). Rearomatization and decoordination of the alkylated phenol followed by oxidation of copper(I) to copper(II) finally close the cycle.…”
Section: Alkylation With Alkylmetal Reagentsmentioning
confidence: 99%
“…[154] Durch die Reaktion mit katalytischen Mengen an Kupfer(II)-acetat und Natriumacetat konnte eine Auswahl an Phenolen in einem offenen Reaktionsgefäßu nabhängig von den elektronischen und sterischen Eigenschaften der Ausgangsphenole glatt aminoalkyliert werden, wobei meta-substituierte Derivate allerdings Gemische an Regioisomeren ergaben. Kaliumaminomethyltrifluoroborate erfüllen diese Anforderung,und die Gruppe von Wang zeigte,dass es sich bei ihnen um effiziente Reagentien fürd ie kupferkatalysierte ortho-Aminomethylierung von Phenolen handelt (Schema 34).…”
Section: Alkylierung Mit Alkylmetallreagentienunclassified
“…Kaliumaminomethyltrifluoroborate erfüllen diese Anforderung,und die Gruppe von Wang zeigte,dass es sich bei ihnen um effiziente Reagentien fürd ie kupferkatalysierte ortho-Aminomethylierung von Phenolen handelt (Schema 34). [154] Durch die Reaktion mit katalytischen Mengen an Kupfer(II)-acetat und Natriumacetat konnte eine Auswahl an Phenolen in einem offenen Reaktionsgefäßu nabhängig von den elektronischen und sterischen Eigenschaften der Ausgangsphenole glatt aminoalkyliert werden, wobei meta-substituierte Derivate allerdings Gemische an Regioisomeren ergaben. Der vorgeschlagene Mechanismus umfasst die Bildung von Kupfer(II)-phenoxid, das nachfolgend an das Stickstoffatom der Aminomethyltrifluoroborate koordiniert.…”
Section: Alkylierung Mit Alkylmetallreagentienunclassified
“…They are employed most frequently in the palladium catalyzed, Suzuki–Miyaura cross‐coupling reactions leading to new C–C bonds , . Organotrifluoroborates are also finding utility as valuable reagents in other metal mediated and metal‐free reactions, and in the C–O and C–N bond coupling processes, and applications including PET imaging work . They are usually synthesized and used as their potassium salts .…”
Section: Introductionmentioning
confidence: 99%